(untitled) (REMUNOM, 2024)
The principle of integral protection of minors is present in the national legal system, assuming great importance since the promulgation of the Federal Constitution of 1988 and the Statute of the Child and Adolescent. With legislative provision, the principle had a prominent role in governing the process of adoption of children and adolescents in the country. As a result, the Civil Code and the Adoption Law, in line with previous laws, began to establish requirements and procedures for adoption in the best possible way, considering its irrevocable nature. However, considering that adoption sometimes conflicts with the principles of integral protection of minors and the best interests of the child and adolescent, in certain cases, the revocation of adoption becomes a measure that best serves these principles, even though it may seem contradictory at first glance. The present study, therefore, seeks, through bibliographic research, notably in doctrines, jurisprudence, and legislation analyses, to examine the possibility of revoking adoption based on respect for the principle of integral protection of minors and the best interests of the child.